Synthesis, Characterization And Antifungal Activity Of 2-[(8-hydroxyquinolinyl)-5-aminomethyl]-3-(4-chlorophenyl)-6-bromo-3(h)-quinazolin-4-one Ligand And Its Transition Metal Chelates - Vashi, R. T.; Patel, S. B. (University of Eloued جامعة الوادي, 2013)
Synthesis and characterization of 2-[(8-hydroxyquinolinyl)-5-aminomethyl]-3-(4-chlorophenyl)-6-Bromo-3(H)-quinazolin-4-one ligand called HAMQ (HL10) was studied. To prepare this ligand anthranilic acid was converted into 5-bromo–N-Chloroacetyl anthranilic acid then into 2-[(8-hydroxyquinolinyl) -5-aminomethyl] -3-(4-chrolophenyl) -6-bromo- 3(H)-quinazolin-4-one. This compound was prepared by condensation with 5-amino-8-hydroxyquinoline. New transition metal chelates of Cu2+, Ni2+, Zn2+, Mn2+ and Co2+ of this ligand HAMQ were prepared and characterized by reflectance, 1H-NMR as well as IR spectroscopy, elemental analysis molar conductance and magnetic measurements. The stoichiometry of the complexes has been found to be 1: 2 (Metal: ligand). The data suggested an octahedral geometry around Co2+, Ni2+ and Mn2+ complexes, a distorted octahedral geometry around Cu2+ and a tetrahedral geometry around Zn2+ have been proposed. The metal complexes were screened for the antifungal activity.
Articale in Journal of fundamental and Applied Sciences Vol. 05 N. 02
Keywords: Ligand, 8-hydroxyquinoline, IR and NMR spectral studies, antifungal activity.